Design Learning Media with an Open-Ended Problem Approach Using the Web to Improve Critical Thinking of Vocational Students - Noviana, Renra; Setiawan, Wawan; Wahyudin, Asep (Universitas Pendidikan Indonesia, 2022)
Critical thinking skills must be provided through education, by developing critical thinking skills to make them better trained in solving various kinds of problems both in learning and outside learning. To improve critical thinking skills, an appropriate learning approach is needed, learning must be student-centered. This study aims to develop instructional media with an open-ended approach measure the improvements on students from the application of media and student responses to the media. This study uses a Comprehensive Life Cycle (SHM) methodology to develop media. One-group pretest post-test was used for the research design. media with an open-ended problem approach have been developed and get a percentage score of 86% or